1913 N.J. Laws 339 - (:unkn) unknown (My University, 1913)
Ch. 186, 1-2: It shall not be lawful for any person or persons, corporation or corporations, to manufacture, sell, barter, exchange, hire, loan, give, buy or have in possession or use or shoot any air gun, spring gun or pistol, or other weapon of a similar nature in which the propelling force is a spring or air and ejecting a bullet or missile smaller than three eighths of an inch in diameter, with sufficient force to injure the person.
Keywords: TRANSFER